Hurdle Approach to Simulate Corn Wet Milling Inactivation of Undesirable Microorganisms: A Pilot Scale Microbial Challenge Study Using Salmonella Surrogate Enterococcus faecium - Erin Kealey; Madeline Shick; Minho Kim; Ruben Chavez; Gordon Shetley; David Stenger; Kirk A. Perreau; Allison Cooke; Cecil Barnett-Neefs; Matthew J. Stasiewicz (Journal of Food Protection)
Corn wet milling (CWM) and corn starch flash drying processing conditions reduce undesirable microorganisms, such as Salmonella. Finished products are historically safe, with intrinsic properties such as low water activity inhibiting microbial growth. Corn processors could use quantified levels of reduction in this study of Salmonella surrogate Enterococcus faecium (E. faecium) to update their food safety plans. Industry-relevant conditions for CWM processes were recreated at pilot or lab scale for 3 unit operations: (1) steeping treatment in sulfur dioxide (SO2) with low (750 ppm SO2, 20 h, 43.3 °C), medium (1,500 ppm SO2, 30 h, 48.9 °C), and high (2,200 ppm SO2, 40 h, 53.3 °C) treatment conditions; (2) hydrogen peroxide (H2O2) treatment tested on bench scale with a factorial design (pH 3.5, 4.0, and 4.5), H2O2 concentrations (0.05%, 0.10%, 0.15% (w/w)), and temperatures (32, 38, and 46 °C) for 3 and 6 h; (3) flash drying treatment at 4 different temperatures (149, 177, 204, and 232 °C) with 2 different inoculation methods. E. faecium was reduced during each of these unit operations. By the end of each steeping treatment, E. faecium was consistently below the limit of quantitation (LOQ), meaning >6.5 log CFU/mL reduction in steep water, and >3.7 log CFU/g reduction in ground corn. The peroxide step had a reduction range from 0.03 log CFU/mL in the control group (0% H2O2 added) to >6 log CFU/mL observed in the high-intensity treatment of corn starch slurry. Flash drying had a reduction range from 1.7 to 2.7 log CFU/g. There was also no biologically meaningful change (<1 log CFU/g reduction) of E. faecium counts during an 8-week survival study of the dried final product. This hurdle approach study shows that existing CWM conditions are effective for Salmonella surrogate reduction through processing into finished starch and provides quantified E. faecium reductions for use in food safety plans.